Governance Factor and Effects of Political Apathy in Nigerian Political Culture: A Prognostic Analysis - CHUKWUDI, Celestina Ekene (Socialscientia: Journal of Social Sciences and Humanities, 2023)
A lot of negative effects accompany political apathy in Nigerian society. When the citizens lose interest in partaking in different forms of political activities in their state or nation, the political development becomes negatively affected. Opportunities avail for unpopular candidates to emerge as winners in an election. The type of leaders that emerge under a situation of apathy are not always accountable to the people in general but to the few that made their emergence to power possible. This position of apathy affects the democratic principles and dividends which invariably shows the level of political culture in the society. This research is embarked upon to explore the dangers that follow the attitude of political apathy among Nigerian citizens, such as bad leaders, bad governance, insensitivity to the plight of the people, and neglect to the principles of democracy. Secondly, the study proffers solutions to political apathy in the society. This study adopts qualitative method where secondary sources as books, journals, magazines and newspapers are used as source materials. In-depth interview of key informants in the society were conducted to get primary information from people in the society. Systems theory was used as the theoretical framework of analysis of the study. The findings show that political apathy has led to emergence of bad leaders. The study concludes that it is difficult to enjoy the dividends of democracy in a society overtaken by political apathy. The study recommends free and fair election, fair playing ground for contestants, and provision of adequate security and prevention of violence.